Mendorong Kemandirian UMKM di Jawa Timur Melalui Inovasi dan Keberlanjutan - Aristyanto, Erwan; Agus Sarwo Edi; Waras (Universitas Muhammadiyah Surabaya, 2025)
The purpose of this research is to formulate a model for the Strategy to Enhance Competitiveness and Sustainability of SMEs in Supporting Independence in East Java. The research method is descriptive qualitative. Data collection techniques include observation, interviews, and documentation. Data analysis techniques use 1) Data reduction, 2) Data display, 3) Data triangulation, 4) Data verification. The informant determination technique uses indepth interviews with key informants such as SME actors, relevant agency officials, representatives from East Java's SME Banks, and academics. The results of data analysis and literature review indicate that the Strategy to Enhance Competitiveness of SMEs in East Java focuses on the adoption of digital marketing (utilization of social media, marketplaces, and e-commerce), product and process innovation (development of unique and quality products, production efficiency), as well as strengthening partnerships and collaborations with various parties (government, financial institutions, large companies) to expand market access and resources. The strategy for enhancing the sustainability of MSMEs in East Java heavily relies on prudent financial management practices (cash flow management, access to affordable financing such as Prokesra and Dagulir), compliance with legal and certification requirements (PIRT, halal, BPOM), as well as the potential implementation of circular economy concepts for resource efficiency and waste reduction. The strategy supporting the independence of MSMEs in East Java focuses on a comprehensive empowerment program, including entrepreneurship training and intensive mentoring for capacity building, ease of access to capital, and facilitation of business matching and exhibitions/bazaars for network and market expansion. The active role of the government and supporting institutions is crucial in creating a conducive ecosystem. The relationship between competitiveness, sustainability, and independence of SMEs is synergistic and mutually reinforcing. Increasing competitiveness directly contributes to economic sustainability. Sustainability creates stability that allows SMEs to continue innovating and enhancing their competitiveness. Meanwhile, independence empowers SMEs to be proactive in achieving competitiveness and sustainability, with the ability to make strategic decisions and adapt to changes. Overall, SMEs in East Java have great potential to continue growing and contributing to the economy. However, sustained support through appropriate policies, relevant empowerment programs, and facilitation of access to essential resources will be key to realizing SMEs that are not only competitive and sustainable but also fully independent Keywords: Strategy for Increasing Competitiveness, Sustainability, Independence.